Três reflexões sobre a direção de arte no cinema brasileiro - Santos Neto, Benedito Ferreira dos (2019)
This research aims to identify and reflect upon the defining characteristics of the emergence of production design in Brazilian film and the procedures it adopted in the following decades. The function, related to the practice of staging, uses the most diverse forms of expression for the elaboration of one or more visualities. It is likely that the first film to assign a credit for production design in Brazil was El Justicero (Nelson Pereira dos Santos, 1967), where Luiz Carlos Ripper is credited as production designer. In 1974, the film A Casa das Tentações, directed by filmmaker and film critic Rubem Biáfora - also responsible for set design - enlists a credit for Rocco Biaggi, possibly a pseudonym of the director himself, as production designer. Also noteworthy is the symbolic art direction of O Gigante da América, directed by Julio Bressane and released in 1978. The thematic diversity of the 1980s, obvious in the filmographies of Walter Hugo Khouri and Hector Babenco, displays an intensity in experimentation, a fertile ground for the development of production designers, set designers and costume designers. However, the actual establishment of the function in Brazilian film really takes place in the 1990s, through the internationalization of productions and the requirement for a "well-finished" image. From this perspective, we believe the film Central Station (Walter Salles, 1998) to disclose important characteristics in the production design of that period.